Jam! : amp your team, rock your business : work hard, rock harder - Carlisi, Jeff (Jossey-Bass, 2009)
"Each chapter of Jam! examines a key moment the development of a band -- formation, early success, internal crises, and so forth -- and demonstrates how you can use those lessons to crank your own business to eleven. You'll also see how the world's best - known bands and singers triumphed over their own challenges, offering useful lessons for everyone in the business world"--Page 3